Penerapan Aplikasi Augmented Reality pada Media Pembelajaran Bangun Ruang di Politeknik Manufaktur Negeri Bangka - Julianti, Rima; Erianti, Agnes; Andriyanto, Sidhiq; Riezky Pratiwi, Indah (Jurnal Inovasi Teknologi Terapan, 2025)
The development of Augmented Reality (AR)-based learning media has become an innovative solution to enhance students' understanding of geometry, especially at Politeknik Manufaktur Negeri Bangka Belitung. This research aims to develop and test the 3DShape-AR application as a learning medium for geometry. The application was developed using the Rapid Application Development (RAD) method, which includes planning, design, implementation, and analysis stages. In addition to serving as a learning medium, the application is equipped with an educational game in the form of quizzes to increase student interactivity. Validation results show that this application is suitable for use, with a user satisfaction rate of 90.34%. These findings support the implementation of AR technology in mathematics learning for geometry at Politeknik Manufaktur Negeri Bangka Belitung.